The status of introduced fish species in Malaysia. - Ang, Kok Jee; Gopinath, N.; Chua, T. E. (1988)
The fate on introduced fish in Malaysia was traced with special refence to their abilities to establish in local conditions. Of the dozen food fish introduced in Malaysia,only Trichogaster pectoralis,Putius gonionotus,tilapias and Clarias macrocephalus were able to establish successfully in local conditions. Other species were able to grow well in local environment but was not able to propagate naturally. Introduced fishes contribute 88% of total freshwater aquaculture production and 72% of total freshwater fish production. Some diseases found with introduced fishes were recorded. Existing laws governing importation of exotic species were examined.